Graphene-Driven Formation of Ferromagnetic Metallic Cobalt Nanoparticles - Saavedra-Díaz, E (Multidisciplinary Digital Publishing Institute (MDPI), 2025)
This work demonstrates the synthesis of ferromagnetic metallic cobalt nanoparticles embedded in a graphene framework through a graphene-assisted carbothermal reduction process. Cobalt oxide (Co3O4) was employed as the starting material, with graphene nanopowder functioning simultaneously as the reducing medium and structural scaffold. Thermal treatment at 850 degrees C under an argon atmosphere triggered the phase transformation. X-ray diffraction (XRD) confirmed the successful conversion of cobalt oxide into face-centered cubic (FCC) metallic cobalt. The graphene network not only accelerated the reduction reaction but also ensured the homogeneous distribution of cobalt nanoparticles within the matrix. Magnetic measurements using vibrating sample magnetometry (VSM) revealed a substantial improvement in ferromagnetic behavior: the graphene-mediated samples reached a saturation magnetization (Ms) of approximately 130 emu/g, compared to the nearly non-magnetic response of cobalt oxide annealed under the same conditions without graphene. Collectively, the structural, compositional, and magnetic results highlight graphene s critical role in driving the formation of metallic cobalt nanoparticles with enhanced ferromagnetism, emphasizing their promise for use in magnetic storage, sensing, and spintronic applications. We anticipate that this study will inspire further research into the dual functionality of graphene, serving as both a reductive agent for metal oxides and a supportive matrix for nanoparticles, toward enhancing the structural integrity and functional properties of graphene-based metal nanocomposite materials.